Topical Capsaicin for Treating Cannabinoid Hyperemesis Syndrome - Ansar Aziz; Tayyab Waheed; Olubunmi Oladunjoye; Adeolu Oladunjoye; Midhat Hanif; Fareena Latif (Case Reports in Gastrointestinal Medicine)
Introduction. Cannabinoid hyperemesis syndrome (CHS), associated with chronic cannabis use, presents with cyclic abdominal pain, nausea, and vomiting. With increasing use of marijuana, the incidence of CHS is expected to increase. Most patients with CHS make frequent visits to the emergency room and are usually refractory to conventional treatment. We, therefore, present a case of CHS successfully treated with topical capsaicin application. Case Presentation. A 41-year-old female with a recent excess use of cannabis presented to the emergency department for evaluation of recurrent excruciating epigastric pain accompanied by severe nausea and vomiting. She had similar, milder symptoms a year ago and underwent endoscopic evaluation which was negative except for mild reflux esophagitis for which she was started on a proton pump inhibitor. On this presentation, basic laboratory workup, EKG, and CT scan of abdomen and pelvis were unremarkable. A detailed abdominal exam was only positive for mild epigastric tenderness. She was instructed to continue pantoprazole and pain medication and outpatient repeat esophagogastroduodenoscopy. The patient returned the next day with extreme retching, nausea, and vomiting and was admitted for further evaluation. Intravenous fluids, antiemetics, and morphine were started for pain control with no symptomatic improvement. A diagnosis of cannabis hyperemesis syndrome was made based on history of chronic marijuana use and otherwise negative workup. A trial of topical capsaicin, over the epigastric region, was tried that provided dramatic relief within 24 hours. Repeat endoscopic evaluation had no evidence of ulcers, celiac disease, or esophagitis. She was discharged on topical capsaicin and counselled on marijuana abstinence, with no return of symptoms. Conclusion. Based on the dramatic resolution of symptoms with topical capsaicin, our case supports this promising intervention and provides an alternate approach to antiemetics and narcotics routinely used in patients with cannabis hyperemesis syndrome.